Assembly, growth and nonlinear thermo-optical properties of nitropeptides1. Issue 26 (14th July 2015) - Bera, Santu; Ambast, Deepak K. S.; Pal, Bipul; Haldar, Debasish
<x xml:space="preserve">Abstract</x> Irrespective of having the same functional group, π-conjugated system, chirality and backbone conformation as nitropeptides 1 and 3, nitropeptide 2 that forms a hydrogen bond and π–π stacking assisted dimer exhibits self-phase modulation.